Global, regional and national trends in the burden of nutritional deficiencies in children, 1990–2021 - Liu, Zhuoqiong; Liu, Yangyang; Yang, Jiaxin; Yan, Liru; Li, Qiushi; Gao, Ying (Frontiers in Nutrition, 2025)
BackgroundThe objective of this study was to systematically assess global, regional, and national trends in the prevalence and burden of nutritional deficiencies among children aged 0–14 years from 1990 to 2021. Specifically, four major subtypes of malnutrition: protein-energy malnutrition, Vitamin A deficiency, iodine deficiency, and dietary iron deficiency.MethodsThis study utilized data from the 2021 Global Burden of Disease (GBD) database to analyze incidence and disability-adjusted life year (DALY) rates. The estimated annual percentage change (EAPC) was calculated, with the data stratified based on age, gender, region, socio-demographic index (SDI), and country.ResultsBetween 1990 and 2021, the global burden of nutritional deficiencies (all ages 0–14 combined) in children declined. The age-standardized DALY rate of dietary iron deficiency had the lowest EAPC (− 0.53; 95% CI: − 0.62, − 0.45). The highest burden of nutritional deficiencies and its subtypes was in Sub-Saharan Africa, but the age-standardized DALY rate of dietary iron deficiency and the age-standardized incidence rate (ASIR) of protein-energy malnutrition were highest in South Asia (1103.19 and 3185.45 respectively). Age-standardized DALYs of protein-energy malnutrition increased substantially in high-income North America (EAPC: 3.30) and Western Europe (EAPC: 2.29). The age group with the greatest burden of nutritional deficiencies and of its subtypes was 0–4 years age group.ConclusionFrom 1990 to 2021, Sub-Saharan Africa has consistently faced the most severe nutritional deficiencies. Meanwhile, South Asia continues to struggle with significant protein-energy and dietary iron nutritional shortfalls. Conversely, high-income North America and Western Europe have experienced a notable rise in protein-energy deficiency.